Implementasi Nilai Kejujuran Dan Tanggung Jawab Dalam Pendidikan Anti Korupsi Pada Siswa - Intan Oktaviani; Bintang Dwi Fadilah; Siti Nurjanah; Nur Fitri Hafni; Zio Pangestu Putra; Emi Angreani Masjur (Educate : Journal of Education and Learning, 2026)
This study aims to describe the implementation of honesty and responsibility values in anti-corruption education among elementary school students. The study employed a descriptive qualitative approach and was conducted at an elementary school in Karawang Regency. The research subjects consisted of five fourth- and fifth-grade students as the main informants and twenty parents as supporting informants. Data were collected through interviews, open-ended questionnaires, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that honesty was implemented through the habits of telling the truth, admitting mistakes, and returning items that did not belong to the students. Responsibility was demonstrated through completing school assignments, carrying out classroom duties, and helping parents at home. The implementation of these values was supported by parental and teacher role models, early habituation, and cooperation between families and schools. Meanwhile, peer influence, excessive gadget use, and social media were identified as inhibiting factors. This study concludes that anti-corruption education through the cultivation of honesty and responsibility has been implemented in students’ daily lives and contributes to the development of integrity from an early age.